The Influence of Demographic Factors and Social Class on Customers' Decisions to Choose Islamic Banks - Dewi Indraswari; Salwa Rumi (Golden Ratio of Data in Summary, 2021)
This study discusses the influence of demographic and social class factors on customers' decisions to choose Islamic banks in Palopo City. On the customer's decision to choose an Islamic bank in the city of Palopo and prove the influence of these factors simultaneously. To provide answers to the problems stated above, the authors use a quantitative research approach with the variables used in this study are the independent variables, namely education, income, employment, dependents, and age as well as the dependent variable in the form of a customer's decision to choose an Islamic bank. This study took 100 respondents using the Non-Probability Sampling method as the sample. Data collection in this study used a questionnaire with regression analysis techniques through the F-test and t-test using the Software Statistical Product and Service Solutions (SPSS) 19.0. The results of the study show that education, income, employment, and age have a significant effect on the customer's decision to choose an Islamic bank in Palopo City. This is evidenced by obtaining a significance value of 0.000 or less than 5% (0.05). The results of the partial statistical test also show that the variables of education, income and employment have a significant positive effect, while the age variable has a significant negative effect on the customer's decision to choose an Islamic bank in Palopo City. Based on the beta regression coefficient, the highest coefficient value is the income variable of 7,060 with a significance level of 0.000. These findings indicate that income is the variable that has the most influence on the customer's decision to choose Islamic Banking among the other four variables. Based on the results of the simultaneous test it was concluded that the independent variables simultaneously represented by the variables of education, income, employment, dependents, and age have a significant effect on the dependent variable on customer decisions.